2000
DOI: 10.1136/heart.83.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Long term consequences of regressed coronary aneurysms after Kawasaki disease: vascular wall morphology and function

Abstract: Objectives-To investigate the long term consequences of regressed aneurysms after Kawasaki disease, using follow up coronary angiography; to assess the vascular wall morphology at the site of the aneurysms by intravascular ultrasound imaging; and to evaluate the function of the aVected vessels using intracoronary infusions of acetylcholine and isosorbide dinitrate. Design-33 patients were studied, 27 with previous Kawasaki disease and six with congenital heart disease. All Kawasaki disease patients were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
144
1
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(157 citation statements)
references
References 27 publications
5
144
1
7
Order By: Relevance
“…The minimal lumen diameter (MLD) was measured before and after the catheter intervention and on follow-up studies with the use of the image analyzing system (CARDIO 500, Kontron Elektronic Corp), according to our previous studies. 12,14 …”
Section: Qca Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The minimal lumen diameter (MLD) was measured before and after the catheter intervention and on follow-up studies with the use of the image analyzing system (CARDIO 500, Kontron Elektronic Corp), according to our previous studies. 12,14 …”
Section: Qca Studymentioning
confidence: 99%
“…11,12 The IVUS examination was performed by use of 30-MHz catheters (3.5F, Boston Scientific Corp). We then measured the thickness of the intima-media complex and calculated the calcification index by use of the following formula: Calcification index (%)ϭ(calcification area/area of intima-media complex)ϫ100.…”
Section: Ivus Studymentioning
confidence: 99%
See 1 more Smart Citation
“…There were no adverse effects from the ACh or any This study addresses for the first time the EC function in the microvasculature of KS patients. EC dysfunction in medium-size muscular arteries in children after recovery from KS has been documented invasively by angiography with ACh infusion and arterial input impedance [3] as well as noninvasively by measurement of brachial artery flow-mediated dilation [5][6][7]10]. Studies have demonstrated elevated levels of von Willebrand factor, selectins (both E and P), and cellular adhesion molecules (ICAM-1, VCAM-1) as potential biomarkers of EC activation or damage during acute KS [17].…”
Section: Discussionmentioning
confidence: 99%
“…Intracoronary injection of acetylcholine (ACh) in children with both persistent and regressed coronary artery aneurysms has demonstrated EC dysfunction with paradoxical vasoconstriction [5][6][7]. However, EC function after recovery from KS in children without coronary artery abnormalities in the acute stage is less clear.…”
mentioning
confidence: 99%